2001
DOI: 10.1002/ijc.1528
|View full text |Cite
|
Sign up to set email alerts
|

Cancer incidence in women with or at risk for HIV

Abstract: The purpose of our study was to identify the types and rates of cancers seen in high-risk human immunodeficiency virus (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(40 citation statements)
references
References 28 publications
0
36
0
Order By: Relevance
“…All 10 studies reported increased risk for lung cancer associated with HIV infection ( Figure 1); in two studies, the estimated risk did not achieve statistical significance. SIRs were generally in the range of a 2-to 3-fold increased risk; two studies reported notably higher risk estimates (29,31). A recent study of HIV-infected and at-risk women reported elevated lung cancer risk in both groups compared with population estimates (37); the unadjusted incidence rate ratio for HIV-infected compared with uninfected women was increased 2-fold, although, with only 14 cases, this estimate was imprecise (95% confidence interval [CI], 0. .…”
Section: Epidemiologic Data On the Association Of Hiv With Lung Cancermentioning
confidence: 95%
See 2 more Smart Citations
“…All 10 studies reported increased risk for lung cancer associated with HIV infection ( Figure 1); in two studies, the estimated risk did not achieve statistical significance. SIRs were generally in the range of a 2-to 3-fold increased risk; two studies reported notably higher risk estimates (29,31). A recent study of HIV-infected and at-risk women reported elevated lung cancer risk in both groups compared with population estimates (37); the unadjusted incidence rate ratio for HIV-infected compared with uninfected women was increased 2-fold, although, with only 14 cases, this estimate was imprecise (95% confidence interval [CI], 0. .…”
Section: Epidemiologic Data On the Association Of Hiv With Lung Cancermentioning
confidence: 95%
“…Although there is a clear and consistent demonstration of elevated lung cancer risk among HIV-infected persons compared with the general population (Figure 1), it cannot be fully determined whether this elevated risk is due solely to heavy smoking in the HIV-infected population. In contrast, five studies have directly accounted for individual smoking exposure among HIV-infected persons and an epidemiologicly appropriate comparison population (Table 3) (3,4,29,41,42). In these studies, the risk for lung cancer associated with HIV infection after adjusting for smoking ranged from a 1.2-to 3.6-fold increase (Figure 2).…”
Section: Epidemiologic Data On the Association Of Hiv With Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…This was followed by reports of a markedly higher risk of developing malignancies such as Kaposi's sarcoma (KS) [2] and [3], primary cerebral and systemically occurring non-Hodgkin lymphoma (NHL) [4], [5], [6], [7] and [8] as well as invasive cervical cancer in those harbouring this virus, although the incidence of the latter malignancy has not increased as dramatically [9] and [10].…”
Section: Introductionmentioning
confidence: 99%
“…Smoking among people with HIV may confer increased risks of medical consequences including development of bacterial pneumonia, cardiovascular disease, emphysema, lung cancer, periodontal disease, oral candidiases, oral hairy leukoplakia, oral lesions, Karposi's sarcoma, and AIDS dementia complex compared to HIV positive non-smokers (Burns et al 1996;Diaz et al 2000;Niaura et al 2000;Palacio et al 1997;Nieman et al 1993;Phelps et al 2001). Smoking is related to increased rates of depression and neurological disease among this HIV positive people, and smoking during pregnancy triples the risk of HIV transmission to the fetus (Niaura et al 2000).…”
Section: Introductionmentioning
confidence: 99%